Surgical treatment of hyperhidrosis - Mérola, Lorenzo; Malosetti, Hugo (Cirugía del Uruguay, 1975)
Essential hyperhidrosis syndrome of the upper limbs is a rare disease, which usually brings forth an important social or laboral impediment. It may perhaps be due to an increase in sympathetic tone, sometimes on a psychosomatic basis. In 2 of the reported cases, it had a familial character. Medical treatment -with anticholinergics- usually has a relative success and undesirable side-effects. Consequently, sympathetic denervation of the upper extremity is preferred. The authors have performed it at pre-ganglionar level, by resection of the 2nd. and 3rd. thoracic ganglia. They used Smithwick's posterior extrapleural approach, Results were very good in the 6 operated patients, and there were no relapses in the series.